Época de desova do cangati, Trachycoryster galeatus (Linnaeus, 1756), no Açude Pereira de Miranda (Pentecoste - Ceará) Spawn period of the cangati, Trachycorystes galeatus (Linnaeus, 1756), into Pereira de Miranda reservoir (Pentecoste - Cear· - Brazil) (Revista Ciência Agronômica, 2023)
RCA